Performance of Al-si-glass fiber composite piston in an IC Engine (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The piston is one of the major part of the automobile. The piston purpose is to transfer force from expanding gas in the cylinder to the crankshaft. The piston acts as the vital link between the generation of power inside the combustion chamber to its transfer to the crankshaft and converting to-and-fro motion into continuous rotary motion. The piston assembly is probably subjected to the widest range of mechanical and thermal stresses. Now a days we using aluminium material for the piston because it having low density, high thermal conductivity and high corrosive resistant when compare to cast iron. One of the major problem in aluminium piston is piston slap. It occurs due to high thermal expansion of the aluminium material so providing more gap between the cylinder and the piston. The thermal expansion coefficient of the aluminium is hardly two to three time higher than the cast iron material. For reducing the thermal expansion coefficient of the aluminium material by adding the composite material which having low thermal expansion coefficient without decreasing the hardness of the material. The glass fiber material having theCoefficient of Expansion in inches of expansion per inch of material per degree Fahrenheit is â€œ2.2â€. The aluminium and the glass fiber melting point are nearly same so it can be easily mixed with each other. By adding the glass fiber to aluminium piston it will increase the thermal and mechanical property of the piston.